2011
DOI: 10.3892/mmr.2011.588
|View full text |Cite
|
Sign up to set email alerts
|

Aged black garlic extract induces inhibition of gastric cancer cell growth in�vitro and in�vivo

Abstract: Abstract. There is mounting evidence that garlic extracts possess significant anticancer actions. However, no studies have been reported on the effects of aged black garlic extracts (ABGE) on gastric cancer in vitro or in vivo. To examine the potential action of ABGE against gastric cancer, the present study evaluated its effect on the inhibition of cell proliferation and induction of apoptosis in SGC-7901 human gastric cancer cells. Additionally, we performed an in vivo study by inoculating the murine foregas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 38 publications
(38 reference statements)
3
57
0
6
Order By: Relevance
“…Aged garlic extract (AGE) is well-documented alternative source of garlic that is odorless and rich in antioxidants [9]. Moreover, it has been reported that AGE may play a role in the mitigation of cardiovascular disease [10,11], inflammation [12], hypertension [13], and cancer risk [14]. To examine the effects of AGE and exercise as a combined treatment, we recently performed a study of the efficacy of AGE and exercise interventions in HFD inducedobesity.…”
Section: Introduction 9)mentioning
confidence: 99%
“…Aged garlic extract (AGE) is well-documented alternative source of garlic that is odorless and rich in antioxidants [9]. Moreover, it has been reported that AGE may play a role in the mitigation of cardiovascular disease [10,11], inflammation [12], hypertension [13], and cancer risk [14]. To examine the effects of AGE and exercise as a combined treatment, we recently performed a study of the efficacy of AGE and exercise interventions in HFD inducedobesity.…”
Section: Introduction 9)mentioning
confidence: 99%
“…Aged black garlic has been generally reported to have excellent antioxidant potency when compared to fresh or cooked garlic. The reason is probably that the bioactivity of some natural products increases during the process of fermentation [17][18][19][20][21][22][23], but no specific experimental proof has yet established its anti-cancer efficacy. In this study, we have demonstrated that HEABG significantly decreased cell proliferation in human leukemic U937 cells by inducing apoptosis, as determined by DAPI staining, agarose gel electrophoresis and flow cytometric analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most useful garlic preparations is aged black garlic, which is produced by aging whole garlic at high temperature and humidity [17]. Previous studies have shown that the extracts of aged black garlic have many pharmacological activities, including antioxidant, radical scavenging and anti-cancer effects [17][18][19][20][21][22]. Recently, Kim et al [23] reported that a hexane extract of aged black garlic (HEABG) potently suppressed the proliferation of tumor necrosis factor (TNF)-α-activated human endometrial stromal cells, through inhibiting the activation of nuclear factor-κB (NF-κB) and activator protein-1 (AP-1) transcription factors.…”
Section: Introduction 2)mentioning
confidence: 99%
“…Berbagai penelitian farmakologi tentang bawang putih telah banyak dilakukan, tidak hanya secara in vivo (dengan hewan percobaan) tetapi juga in vitro (dalam tabung kultur). Berbagai penelitian yang telah dikembangkan menunjukkan bahwa bawang putih mempunyai efek biologis dan farmakologis seperti antitumorigenesis, antianteroskleriosis, modulasi gula darah dan antibiosis, penghambatan pertumbuhan kanker (Wang et al, 2011), antihipertensi (Qidwai et al, 2000), aktivitas anti-oksidatif (Borek, 2001), antibakteri (dari isolasi jamur endofit pada bawang putih) (Hidayanti 2010), mencegah perkembangan metastasis tumor (Hu et al, 2002), peningkatan aktivitas fibrinolisis (Pizorno dan Murray, 2000), menghambat pertumbuhan bakteri Salmonella enteritidis, Staphylococcos aureus, dan Salmonella typhosa (Poeloengan, 2001). Selain itu, bawang putih juga dapat menurunkan gejala aflatoksin (Maryam et al, 2003).…”
Section: Pendahuluanunclassified